2001
DOI: 10.1038/sj.onc.1204294
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppression and potentiation by manipulation of pp32 expression

Abstract: Alternative use of genes of the closely-related pp32 family is a common occurrence in human prostate cancer. pp32r1 and pp32r2, the oncogenic members of the pp32 family, are expressed in prostatic adenocarcinoma, while adjacent benign prostate continues to express pp32. This study focuses upon the role of pp32 in tumor suppression. We demonstrate that antisense inhibition of pp32 in NIH3T3 cells leads to a variety of phenotypic changes associated with transformation including reduced serum dependence and loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 20 publications
1
59
0
Order By: Relevance
“…The greatest difference in favor of IGF-II was observed for acidic nuclear phosphoprotein 32 (ANP32) gene (40). ANP32 is a protein involved in embryogenesis that is switched off in differentiated cells.…”
Section: Differential Transcriptional Effects Of Insulin and Igf-ii 4mentioning
confidence: 99%
“…The greatest difference in favor of IGF-II was observed for acidic nuclear phosphoprotein 32 (ANP32) gene (40). ANP32 is a protein involved in embryogenesis that is switched off in differentiated cells.…”
Section: Differential Transcriptional Effects Of Insulin and Igf-ii 4mentioning
confidence: 99%
“…It has been shown that PHAPI can combat Ras and Myc-induced oncogenic transformation and that its highly acidic COOH terminus is necessary for this function (37,38). In addition, PHAPI has been implicated as an inhibitor of protein phosphatase 2A, a modulator of interactions between microtubules and associated proteins, and a regulator of histone acetylation (39)(40)(41).…”
Section: Pp2amentioning
confidence: 99%
“…LANP is also abundant in selfrenewing stem cell-like populations and cell subtypes known for their rapid proliferative ability, such as intestinal crypt epithelial cells and prostatic epithelial cells competent for cell renewal (19,39). There is also some evidence to suggest that LANP and its family members regulate the proliferation of tumor cells (2,6,(13)(14)(15). Incidentally, the SET gene was originally identified as a putative oncogene, identified as the locus for a translocation breakpoint event in acute undifferentiated leukemia, although the cellular basis for oncogenesis is far from clear.…”
mentioning
confidence: 99%